A social study on the health case of Lattakia city 2017-2020 (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This research aims to identify the reality of  health services in Lattakia governorate in light of the crisis and the war on Syria, and how the population displacement affected the service reality of the governorate as it is one of the safest governorates, in addition to identifying what was mentioned in some reports and statistical offices about the . ,  identifying the service situation of hospitals in Lattakia governorate during the crisis, in terms of the lack of medicines and medical staff, and the increase in the need for medical services as a result of the increase in the number of arrivals to the governorate, and arriving at a set of results and scientific recommendations